Ethnobiology of Mountain Communities in Asia -A Book Review - Malik, Zubair A. (Ethnobotany Research and Applications, 2022)
Ethnobiology of Mountain Communities in Asia, Abbasi, A. M., & Bussmann, R. W. (Eds.). (2021) Springer Nature Switzerland. xiv + 439 pp. (Hardcover). EUR 149.99. ISBN: 978-3-030-55493-4; DOI: https://doi.org/10.1007/978-3-030-55494-1 The book under review (Ethnobiology of Mountain Communities in Asia) is a part of the book series, Ethnobiology. So far, twelve volumes of this series have been published since 2015 (https://www.springer.com/series/11551). Ethnobiology is the study of the dynamic relationship between plants, animals, people, and the environment. Contemporary ethnobiological research is grounded in respect for all cultures, embracing the principles of prior informed consent, benefit sharing, and general mindfulness.